ANALISIS KOMUNIKASI, KERJASAMA TIM DAN KEPEMIMPINAN DALAM MENDUKUNG KINERJA PEGAWAI (Studi pada Pegawai Kantor BKPSDM Kabupaten Bireuen) - Irmayani, Irmayani; Iba, Zainuddin (LPPM-UNIKI, 2024)
Research was conducted at the Bireuen Regency Personnel and Human Resources Development Agency (BKPSDM) Office, to examine the impact of communication, teamwork and leadership on supporting employee performance levels. In the form of quantitative research with verification type and data collection through questionnaires. Inferential analysis was used with a path analysis model approach. The results showed that (a) the contribution of communication, teamwork and positive leadership factors to employee performance, respectively, had a large direct and indirect influence of 41.34%, 34.74% and 38.4%. (b) Simultaneously communication, teamwork and leadership influence the performance of Bireuen Regency BKPSDM employees by 64.10%.